Cold sprayed Cu/Invar alloy composite - D.L. Ouyang; Z.R. Wang; T. Yang; L.W. Zhang; D. Wu; W.F. Chen; Q. Hu; S. Guo (Journal of Materials Research and Technology)
Cold spray, an additive manufacturing technique based on plastic deformation of particles, was employed to prepare Cu/Invar alloy composites to avoid issues from other preparation methods, like undesirable thermal expansion anisotropy from the extrusion method and the excessive inter-diffusion between Cu and the Invar alloy from the sintering method. For the target Cux(Fe64Ni36)100-x(x = 30–70, wt%) composites prepared by cold spray, the improved thermal expansion anisotropy was reflected by the negligible difference between the thermal expansion coefficient α along and perpendicular to the spray direction, and simultaneously no obvious inter-diffusion was observed between Cu and the Invar alloy Fe64Ni36 after annealing at 500 °C. Both α and the thermal conductivity λ increased slightly due to the release of internal stress and recrystallization of Cu. α of the annealed composites basically agreed with the theoretical predication, but λ was far below the values predicted by the Hasselman–Johnson model, mostly because the Invar alloy had an extraordinarily large surface area caused by impact deformation. Even so, the cold-sprayed Cu/Invar alloy composites had clearly advantageous comprehensive performance than those prepared by the traditional sintering and melting methods. Among Cu/Invar alloy composites prepared by different methods, the annealed Cu50(Fe64Ni36)50 was the only composite having λ larger than 100 W/m∙K and isotropic α smaller than 10 × 10−6/oC. In addition, the cold-sprayed Cu/Invar alloy composites had a good plasticity (after annealing) that is rarely seen in traditional Cu-based composites with high thermal conductivity, presenting a good application potential for electronic packaging materials.